PENGARUH MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFAE) TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS V DI SD MUHAMMADIYAH 5 - Nopiana, Silvia; Jenal Mutaqin, Ejen (Pendidikan Guru Sekolah Dasar Institut Pendidikan Indonesia Garut, 2020)
This research is motivated by the low learning motivation of the students influenced by the weak implementation of the learning process at schools. Starting with the description above, the problem in this study is